PENERAPAN PUPUK ORGANIK DALAM MENINGKATKAN HASIL PERTANIAN DAN PETERNAKAN SERTA PEREKONOMIAN MASYARAKAT DI DESA SUKARAMAI - Arifa Pratami; Irine Ika Wardhani; Linda Ajliana; Fadhilah Harahap; Alivia Nurul Annisah (Jurnal Pengabdian Mitra Masyarakat, 2022)
Suka Ramai Village as an area rich in natural resource potential including agricultural resources, especially horticulture and livestock. The problem faced by the community in the agricultural sector is the lack of skills on procedures for increasing agricultural products. For these problems, the solution is to conduct training and community assistance in the application of integrated crop farming technology and the introduction of organic fertilizers. Organic fertilizers play a role in increasing plant fertility. The quality and composition of organic fertilizers varies depending on the basic ingredients of the compost and the manufacturing process. The use of organic fertilizers has been applied in organic farming cultivation systems and rice/palawijaya crop systems